Filmes de titânio-silício preparados por spin e dip-coating - Nassar, Eduardo J.; Ciuffi, Katia J.; Gonçalves, Rogéria R. [UNESP]; Messaddeq, Younes [UNESP]; Ribeiro, Sidney José Lima [UNESP] (Sociedade Brasileira de Química, 2003)
The conditions for the preparation of luminescent materials, consisting of Eu3+ ions entrapped in a titanium matrix, in the forma of a thin film, using the sol-gel process, are described. The films were obtained from sols prepared with TEOS and TEOT, in the presence of acetylacetone as the hidrolysis-retarding agent, using the dip-coating and spin-coating techniques. The influence of these techniques on the films based on titanium and silicon are presented. The Eu3+ was used as a luminescent probe. The films have been characterized by luminescence, reflection and transmittance. The thickness of the films could be related to the preparation procedure. Transparent thin films have been prepared by dip-coating technique.
Titanium-silicon films prepared by spin and dip-coating
Keywords: sol-gel; europium III; wave guides